2010
DOI: 10.1007/s12122-009-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temporary Employment on Unemployment Exits in a Competing Risks Framework

Abstract: Unemployment exits, Temporary employment, Competing risks model, Unobserved heterogeneity, J64, J65,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
4
17
0
1
Order By: Relevance
“…As expected, an unemployed person in a region with a high unemployment rate has a smaller probability of receiving a job offer and therefore a longer unemployment spell than a similar person in a region with a low unemployment rate. This is consistent with other findings for Spain like Arranz and Muro (2004), Alba et al (2012), Arranz et al (2010) and Bover, Arellano and Bentolila (2002).…”
Section: Local Unemployment Ratesupporting
confidence: 94%
See 3 more Smart Citations
“…As expected, an unemployed person in a region with a high unemployment rate has a smaller probability of receiving a job offer and therefore a longer unemployment spell than a similar person in a region with a low unemployment rate. This is consistent with other findings for Spain like Arranz and Muro (2004), Alba et al (2012), Arranz et al (2010) and Bover, Arellano and Bentolila (2002).…”
Section: Local Unemployment Ratesupporting
confidence: 94%
“…An exit to any job is 30% more likely for a man than for an otherwise similar woman during the expansion period, and only 17% in the recession. Similar results are found by Arranz and Muro (2004), Arranz et al (2010) and in Alba et al (2012) for exits to new jobs (not recalls). The estimates distinguishing exits to stable and unstable jobs show that before the crisis, the gender difference was much larger for unstable than for stable jobs.…”
Section: Personal Characteristicssupporting
confidence: 85%
See 2 more Smart Citations
“…Arranz et al (2010), for example, showed that temporary workers who became unemployed at the end of their temporary contract are more likely to exit unemployment through another temporary contract than through permanent employment. In the same vein De Graaf-Zijl et al (2010) found that although previous employment in a temporary job shortens unemployment spells, temporary workers do not have better prospects for finding a permanent job in the years after their unemployment.…”
Section: Prior Researchmentioning
confidence: 99%